Analysis and modelling of a permanent magnet biased inductor used in motor drive systems - Zuccherato, M.; Zare, Firuz (2015)
© 2015 EPE Association and IEEE. In this paper, a permanent magnet biased inductor has been analysed and designed for a frequency converter. Line current harmonic and conducted emission tests have been carried out to compare the performance of the hybrid inductor. The analysis shows that the hybrid inductor can have volume reduction in comparison with a traditional inductor.